A Study of Mutation Breeding of High-Yielding Tryptophanase Escherichia coli by Low-Energy N^＋ Ion Beam Implantation - 庞敏 姚建铭 王冬梅 (Plasma science & technology, 2009)
Low energy ion beam has been widely applied in microbe breeding, plant breeding, gene transfer and cell modification. In this study, the Escherichia coli （E.coli） strain producing tryptophanase was irradiated by a low energy nitrogen ion beam with an energy of 10 keV at a fluence of 13 × 10^14 N^＋/cm^2 when glycerin at a 15% concentration was used as a protector. The effect on the biomass of E. coli after N^＋ implantation was analyzed in detail by statistic methods. The screening methods used in this study were proven to be effective. After continuous mutagenicity, a high-yield tryptophanase strain was selected and both its biomass and enzymatic activity were higher than those of the parent strain. The results of scale-up production showed that the biomass could reach wet weight 8.2 g/L and 110 g L-tryptophan could be formed in the volume of the 1 l enzymatic reaction system.